Associations between frailty, sociodemographic characteristics and quality‐of‐life among community‐dwelling older adults: A cross‐sectional study - Lijuan Xu; Xuefen Lan; Yan Lou; Maria Engström (Nursing Open, 2023)
Abstract Aim To explore the quality‐of‐life among community‐dwelling older adults in China and to examine the associations between frailty, sociodemographic characteristics and quality‐of‐life. Design A cross‐sectional correlational study was adopted. Methods Questionnaire study of 311 community‐dwelling older adults using the Life Satisfaction Questionnaire and FRAIL scale. Results Highest quality‐of‐life was found for the physical symptoms factor and the lowest for quality of everyday activities/fun. Frailty was associated with total quality‐of‐life and the physical symptoms and sickness impact factors. For total quality‐of‐life, the odds of being in the group with a median score or more decreased for frail older people (OR 0.30) versus non‐frail and increased for those with medical insurance from employer versus basic (OR 2.30) and those doing exercise ≥30 min 3 days/week or more versus less (OR 2.12). Registered nurses caring for community‐dwelling older adults should screen for and prevent frailty and encourage exercise to improve their quality‐of‐life.